(x + 4)(x + 1)
The value of X after simplifying fully xsquared -16 3xsquared plus 10x -8 is either 2 or 4.
(x + 9)(x + 4)
(x - 7)(x + 2)
It is: 3x
It is: 2xsquared+14x-9
X= 1.567764363, -9.567764363
x2 - 4x + 3 is already in standard form.
Quadratic - the degree is two.
5+5=57k+xsquared divided by the cubed root of 76.348206 repeating.
It is: (x+58.301651611)(x-8.301651611) with the help of the quadratic equation formula
(x-2)(x-4) x=2,4 ans
The GCF is 9xyThe LCM is 36x2y3
find factors of -3 (3 & -1 ) also add together to get 2 (for the 2x part) put x on both sides (x+3) (x-1) << because xsquared means x times x check it 3 times -1 = -3 3 times x = 3x -1 times x = -1x x times x = xsquared = xsquared + 2x -3 hope this helped =)
it is a combination of perfect squares the square of 9x is squared is +/- 3x, and the square of 4 is +/- 2 so the answer is (3x+2)(3x-2) which is 9xsquared-6x+6x-4 =9xsquared-4
x2+7x+12=0usually this means to factor the equation.factored this equation would be...(x+3)(x+4)
x times x